Gender Equality in Interface Organizations between Science, Technology and Innovation - Vehviläinen,Marja (Universidad Alberto Hurtado. Facultad de Economía y Negocios, 2010)
The article addresses the question of gender equality in the context of interface organizations between science, technology and innovation, focusing on gendered work practices in science parks. Drawing upon the notions of gendered work practices, feminization of work and feminist science and technology studies, the article explores: 1. Key aspects of work practices in science parks; 2. Gender segregation embedded in these practices; and 3. Practices which help to promote gender equality in intermediary work. The study is empirically based on interviews with top managers and female experts of four Finnish science parks, complemented by one focus group interview with representatives of funding agencies, ministries and intermediary organizations. The study demonstrates that work in science parks is simultaneously future-oriented knowledge work and service work characterized by features of feminization and care (i.e. sensitivity to the needs of clients). Gender segregation commonly seen in the science, technology and innovation sector is reproduced in novel ways in the work practices of the science parks, especially due to the gendered patterns of professional recognition and male networking. This implies that - in spite of the feminised work practices - women do not find easy careers in science parks. The data show, however, that there are also several practices which are used to counteract segregation and promote gender equality, including a number of positive actions developed by women themselves in order to promote recognition and networking in science parks.